SARS-CoV-2 Infection in Healthcare Professionals and General Population During "First Wave" of COVID-19 Pandemic: A Cross-Sectional Study Conducted in Sicily, Italy - Claudio Costantino; Claudio Costantino; Emanuele Cannizzaro; Maria Gabriella Verso; Fabio Tramuto; Fabio Tramuto; Carmelo Massimo Maida; Carmelo Massimo Maida; Guido Lacca; Davide Alba; Livia Cimino; Arianna Conforto; et al. (Frontiers Media S.A., 2021)
On December 31, 2019, an outbreak of lower respiratory infections was documented in Wuhan caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Since the beginning, SARS-CoV-2 has caused many infections among healthcare workers (HCWs) worldwide. Aims of this study were: a. to compare the distribution among the HCWs and the general population of SARS-CoV-2 infections in Western Sicily and Italy; b. to describe the characteristics of HCWs infected with SARS-CoV-2 in the western Sicilian healthcare context during the first wave of the epidemic diffusion in Italy. Incidence and mean age of HCWs infected with SARS-CoV-2 were comparable in Western Sicily and in the whole Italian country. The 97.6% of infections occurred in HCWs operating in non-coronavirus disease 2019 (COVID-19) working environments, while an equal distribution of cases between hospital and primary care services context was documented. Nurses and healthcare assistants, followed by physicians, were the categories more frequently infected by SARS-CoV-2. The present study suggests that healthcare workers are easily infected compared to the general population but that often infection could equally occur in hospital and non-hospital settings. Safety of HCWs in counteracting the COVID-19 pandemic must be strengthened in hospital [adequate provision of personal protective equipment (PPE), optimization of human resources, implementation of closed and independent groups of HCWs, creation of traffic control building and dedicated areas in every healthcare context] and non-hospital settings (influenza vaccination, adequate psychophysical support, including refreshments during working shifts, adequate rest, and family support).